Catalytic properties of Sr2Ni0.75Mg0.25MoO6–δ based composites for application in hydrocarbon-fuelled solid oxide fuel cells. (10th May 2021) - Skutina, L.S.; Vylkov, A.I.; Bainov, I.N.; Chistyakov, K.A.; Kuznetsov, D.K.; Pavlenko, O.B.; Medvedev, D.A.
Abstract: One of the key directions for the development of commercial solid oxide fuel cells fuelled by natural gases consists in the search for efficient fuel electrode materials operated under hydrocarbon-containing atmospheres. Within the present work, we synthesized and characterised novel composites based on a double-perovskite Sr2 Ni0.75 Mg0.25 MoO6–δ phase and a second phase comprised of SrMoO4 or NiO. For these composite materials, the reduction behaviour, tolerance to carbon dioxide and catalytic activity towards the partial oxidation of hydrocarbons mixture were comprehensively studied. It is shown that the target properties of the designed composites are affected not only by the type of catalysts but also by the method of their preparation. According to the presented results, the most appropriate materials are composites containing 20 wt% SrMoO4 or 50 wt% NiO. Highlights: Sr2 Ni0.75 Mg0.25 MoO6–δ (SNMMO) and its composites with NiO or SrMoO4 were prepared. The chemical stability of these composites against CO2 were studied. The composites were tested as catalysts in biogas partial oxidation process. SNMMO+20 wt% SrMoO4 and SNMMO+50 wt% NiO are good catalysts.